The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1167/iovs.06-0998
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Human Conjunctival and Corneal Epithelial Gene Expression with Oligonucleotide Microarrays

Abstract: Comparative gene expression profiling leads to the identification of many biological processes and previously unknown genes that are potentially active in the function of corneal and conjunctival epithelia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 48 publications
2
49
0
Order By: Relevance
“…Cartilage acidic protein 1 (CRTAC1) is a matrix component with high affinity for integrins. It is profusely expressed in cartilage, a mostly avascular tissue [27]. The corneal expression of CRTAC1 indicated that its function may be related to the avascular environs.…”
Section: +mentioning
confidence: 99%
“…Cartilage acidic protein 1 (CRTAC1) is a matrix component with high affinity for integrins. It is profusely expressed in cartilage, a mostly avascular tissue [27]. The corneal expression of CRTAC1 indicated that its function may be related to the avascular environs.…”
Section: +mentioning
confidence: 99%
“…Actually, a small cluster of cytochrome P450 genes at 7q22.1 (CYP3A4, CYP3A5 , CYP3A7 , and CYP3A43) was deleted in our patient; in fact, most of the deletions in 7q associated with glaucoma or other ocular abnormalities such as cloudy corneas, macrocornea or abnormal pupils involved q22 and likely, CYP s genes [Young et al, 1984;Montgomery et al, 2000]. Remarkably, CY-P3A43 was found differentially expressed in human cornea epithelium tissue [Turner et al, 2007]. In general, members of the subfamily 3A were found expressed in human iris, ciliary body and cornea [Zhang et al, 2008;Volotinen et al, 2011].…”
Section: Discussionmentioning
confidence: 62%
“…5B) produced a transitory increase in negative current to Ϫ8.7 Ϯ 1.2 A⅐cm Ϫ2 (n ϭ 4 conjunctivae; P Ͻ 0.05), a 7% rise that was followed by a gradual current decline. 36 Cl Ϫ fluxes across conjunctivae in the direction of the Cl Ϫ gradient. To corroborate the electrical results with the transepithelial Cl Ϫ gradient, 36 Cl Ϫ was added to the high-Cl Ϫ apical side bath and unidirectional fluxes were measured in the apical-to-basolateral direction for 1 h under baseline conditions, followed by three sequential, 1-h periods in which nystatin, EBIO, and glibenclamide were introduced to the bathing solutions (Table 2).…”
Section: Resultsmentioning
confidence: 99%